Research design and methods a process approach - Bordens, Kenneth S.; Abbott, Bruce B. (McGraw-Hill Education, 2018)
Takes students through the research process, from getting and developing a research idea, to designing and conducting a study, through analyzing and reporting data. Information on the research process is presented in a lively and engaging way, highlighting the numerous decisions that must be made when designing and conducting research.